Health implications of the rapid rise of data centers in Virginia: an exploratory assessment - Gour, Neha; Ortiz, Luis; Maibach, Edward (Frontiers in Climate, 2026)
Driven by advances in cloud computing, cryptocurrency, and artificial intelligence, the rapid proliferation of data centers may pose severe human and planetary health risks. This paper, to the best of our knowledge, is the first-of-its-kind assessment of the potential health implications associated with data centers. Here, we examine the case of Virginia’s Data Center Alley, the world’s largest concentrated data center hub, and argue that data centers can cause public health harms, harms that can be at least partially mitigated through improved planning and design. We assess the health risks associated with data centers, including air pollution, extensive water use, noise pollution, and detrimental land use’s risk of disrupting natural ecosystems and community well-being. We also address how rising energy costs can worsen social determinants of health. To mitigate these risks, we recommend transitioning data centers to renewable energy, implementing strict regulations to minimize water consumption, and optimizing site planning with acoustic treatments and green zoning to reduce noise pollution. Additionally, we advocate enforcing responsible site selection and zoning regulations to curb adverse land use changes, equitable energy pricing to alleviate economic burdens, and strengthening health communication for informed public and governmental decision-making, action-oriented advocacy, and policy changes. Finally, we emphasize the need for transdisciplinary research integrating physical sciences, engineering, and public health to quantify specific health outcomes linked to data centers.